2014
DOI: 10.1371/journal.pone.0087536
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with N- and C-Terminal Peptides of Parathyroid Hormone-Related Protein Partly Compensate the Skeletal Abnormalities in IGF-I Deficient Mice

Abstract: Insulin-like growth factor-I (IGF-I) deficiency causes growth delay, and IGF-I has been shown to partially mediate bone anabolism by parathyroid hormone (PTH). PTH-related protein (PTHrP) is abundant in bone, and has osteogenic features by poorly defined mechanisms. We here examined the capacity of PTHrP (1–36) and PTHrP (107–111) (osteostatin) to reverse the skeletal alterations associated with IGF-I deficiency. Igf1-null mice and their wild type littermates were treated with each PTHrP peptide (80 µg/Kg/ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 74 publications
3
17
0
Order By: Relevance
“…This was not surprising, considering the ability of this peptide to reduce the number of trabecular osteoclasts when administered subcutaneously, as recently reported [45], and the observed increase in OPG/RANKL mRNA ratio induced by PTHrP (107-111)-loaded HA Glu scaffolds in osteoblast cultures in this work. In fact, PTHrP (107-139) has consistently been shown to display anti-resorptive features in rodents [17,[20][21][22], apparently by interacting with osteoclasts directly or indirectly through targeting osteoblasts [19,23,26,28].…”
Section: Discussionsupporting
confidence: 88%
“…This was not surprising, considering the ability of this peptide to reduce the number of trabecular osteoclasts when administered subcutaneously, as recently reported [45], and the observed increase in OPG/RANKL mRNA ratio induced by PTHrP (107-111)-loaded HA Glu scaffolds in osteoblast cultures in this work. In fact, PTHrP (107-139) has consistently been shown to display anti-resorptive features in rodents [17,[20][21][22], apparently by interacting with osteoclasts directly or indirectly through targeting osteoblasts [19,23,26,28].…”
Section: Discussionsupporting
confidence: 88%
“…Results from an early study in ovariectomized rats indicate that daily s.c. injection of osteostatin (18 lg/kg) for 13 days restored the decreased femoral bone mass, apparently through its effect on cortical bone [61]. Consistent with these early findings, we recently found that a clear osteogenic effect was achieved in the long bones of normal mice by administering for 2 weeks a high dose of osteostatin displaying anti-resorptive features [29]. Interestingly, the bone anabolic activity of osteostatin-similar but not identical to that of PTHrP (1-36) using a similar administration regime-was apparent in trabecular bone of mice with IGF-I deficiency and a low bone resorption status [29].…”
Section: C-terminal Pthrp Peptidessupporting
confidence: 81%
“…In particular, the increase in the number of osteoblasts induced by this PTHrP peptide observed in these models seemed to be a consequence of both an increased osteogenic capacity-associated with decreased adipogenesisof the bone marrow and a diminished osteoblast apoptosis [31,56,57]. Our group also recently demonstrated that this type of short treatment of young adult mice with the same PTHrP analog was efficient for improving various cortical bone parameters, but this was not observed in Igf1-null mice, similar to what occurs for the PTH anabolic action [29]. Another recent study has compared the osteogenic capacity of PTHrP (1-34) and PTHrP (1-84) administered at the same equivalent dose (10 nmol/kg) for 4 weeks to ovariectomized mice.…”
Section: Pre-clinical Studies N-terminal Pthrp Analogsmentioning
confidence: 61%
See 1 more Smart Citation
“…11 Interestingly in this regard, systemic administration of N-or C-terminal PTHrP peptides has been reported to reverse at least in part the alterations in bone structure and/or osteoblast differentiation and function in a well characterized type 1 DM mouse model and in Igf1-null mice. [12][13][14] Moreover, we previously showed that osteostatin coating onto various implant types of ceramics or even porous titaniums accelerates healing of critical and non-critical bone defects in the long bones of adult rabbits and rats. 15,16 These observations prompted us to evaluate and compare the efficacy of different PTHrP peptides to promote bone regeneration in a combined aging and DM scenario using a well characterized diabetic model.…”
Section: Introductionmentioning
confidence: 99%